Cost implications of implementation of pathogen‐inactivated platelets. Issue 10 (18th May 2015) - McCullough, Jeffrey; Goldfinger, Dennis; Gorlin, Jed; Riley, William J.; Sandhu, Harpreet; Stowell, Christopher; Ward, Dawn; Clay, Mary; Pulkrabek, Shelley; Chrebtow, Vera; Stassinopoulos, Adonis
<x xml:space="preserve">Abstract</x> BACKGROUND Pathogen inactivation (PI) is a new approach to blood safety that may introduce additional costs. This study identifies costs that could be eliminated, thereby mitigating the financial impact. STUDY DESIGN AND METHODS Cost information was obtained from five institutions on tests and procedures (e.g., irradiation) currently performed, that could be eliminated. The impact of increased platelet (PLT) availability due to fewer testing losses, earlier entry into inventory, and fewer outdates with a 7‐day shelf life were also estimated. Additional estimates include costs associated with managing 1) special requests and 2) test results, 3) quality control and proficiency testing, 4) equipment acquisition and maintenance, 5) replacement of units lost to positive tests, 6) seasonal or geographic testing, and 7) health department interactions. RESULTS All costs are mean values per apheresis PLT unit in USD ($/unit). The estimated test costs that could be eliminated are $71.76/unit and a decrease in transfusion reactions corresponds to $2.70/unit. Avoiding new tests (e.g., Babesia and dengue) amounts to $41.80/unit. Elimination of irradiation saves $8.50/unit, while decreased outdating with 7‐day storage can be amortized to $16.89/unit. Total potential costs saved with PI is $141.65/unit. Costs are influenced by a variety of factors specific to institutions such as testing practices and the location in which such costs are incurred and careful analysis should be performed. Additional benefits, not quantified, include retention of some currently deferred donors and scheduling flexibility due to 7‐day storage. CONCLUSIONS While PI implementation will result in additional costs, there are also potential offsetting cost reductions, especially after 7‐day storage licensing.